1987
DOI: 10.1056/nejm198703263161303
|View full text |Cite
|
Sign up to set email alerts
|

Measles Outbreak in a Fully Immunized Secondary-School Population

Abstract: An outbreak of measles occurred among adolescents in Corpus Christi, Texas, in the spring of 1985, even though vaccination requirements for school attendance had been thoroughly enforced. Serum samples from 1806 students at two secondary schools were obtained eight days after the onset of the first case. Only 4.1 percent of these students (74 of 1806) lacked detectable antibody to measles according to enzyme-linked immunosorbent assay, and more than 99 percent had records of vaccination with live measles vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(40 citation statements)
references
References 19 publications
0
38
1
1
Order By: Relevance
“…This difference is probably explained by lower antibody titre after vaccination (or more rapid antibody loss) than after natural infection [24]. A cohort study in Finland demonstrated that vaccine induced measles antibodies declined more rapidly in the absence of natural boosting than expected [25].…”
Section: Discussionmentioning
confidence: 99%
“…This difference is probably explained by lower antibody titre after vaccination (or more rapid antibody loss) than after natural infection [24]. A cohort study in Finland demonstrated that vaccine induced measles antibodies declined more rapidly in the absence of natural boosting than expected [25].…”
Section: Discussionmentioning
confidence: 99%
“…In outbreaks occurring between 1985 and 1986, 60 % of cases were due to vaccine failure, with vaccination prior to 12 or 15 months of age and vaccinations before 1979 (when the vaccine was less heat stable), being identified as risk factors [4,7,9]. There was, by contrast, no evidence of vaccine failure in our outbreak.…”
Section: Vaccine Efficacymentioning
confidence: 62%
“…Of 1408 questionnaires 1174 (83%) were returned ( 4 cases the history was unknown, and in a further 4 cases parents gave a history of vaccination which was not confirmed by the records. There were no cases with documented evidence of vaccination and a negative parental history.…”
Section: School Studiesmentioning
confidence: 99%
See 2 more Smart Citations